Power Ultrasound Assisted Design of Egg Albumin Nanoparticles - Arzeni, Carolina (2015)
The objective of this work was to develop egg white (EW) nanoparticles by application of high intensity ultrasound (HIUS) at different solution pHs and treatment temperatures. At pH 7 HIUS without heating decreased the particle size. In contrast, the use of thermosonication (TS) increased the particle size. At pH 3, the application of both HIUS and TS induced a significant reduction of particle size. at pH 7 zeta potential did not vary significantly when native solutions were sonicated without heating; however a great decrease was observed when TS or heating were applied. At pH 3, sonication decreased the zeta potential of particles but TS or heating increased the charge. By applying TS (85 °C, 20 min and pH 3) a bimodal distribution was obtained, including particles of 295 and 70 nm of diameter. At the same pH, without heating, a monomodal population of 220 nm of diameter was obtained.